Vehicular Tire as Potential Adsorbent for the Removal of Polycyclic Aromatic Hydrocarbons. (8th August 2018) - Gupta, Himanshu; Gupta, Bina
ABSTRACT: Polycyclic aromatic hydrocarbons (PAHs) are environmental pollutants, entering into various water and wastewater systems through various natural and anthropogenic activities. The aim of the work is to convert vehicular tires, a highly available waste material, into potential adsorbent for the removal of PAHs from aqueous solutions. The BET surface area of the prepared vehicular tire activated carbon is 643.86 m 2 /g. Removal of PAHs using activated carbons and the effect of various parameters such as contact time, adsorbent dose, temperature, and pH on the adsorption have been evaluated. The data were fitted to Freundlich and Langmuir isotherms and values of various constants were evaluated. In all the cases, Freundlich model was found to be better fitted. The equilibrium time for adsorption of PAHs was 120 min. The values of thermodynamic parameters, such as Gibb's free energy change ΔG°, enthalpy change ΔH°, and entropy change ΔS°, were calculated using adsorption equilibrium constants obtained from Langmuir isotherm. The thermodynamic data for adsorption of PAHs revealed spontaneity and endothermic nature of the adsorption process. The samples were analyzed using a UV–vis spectrophotometer for PAH determination. Mixture of sodium hydroxide and ethanol in different proportions was tried for desorption of PAHs and 50% ethanolic NaOH solution was most effective. The developed activated carbon demonstrates good adsorption and desorption capabilities for PAHs, indicating towards its suitability for use in the treatment processes of various industrial effluents or water streams containing PAHs.